Pengembangan Model Ontologi Cerita Rakyat Bali - Budiantari, Ni Made Julia; Sanjaya ER, Ngurah Agus (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 1 No 3 (2023): JNATIA Vol. 1, No. 3, Mei 2023DO - 10.24843/JNATIA.2023.v01.i03.p23, 2023)
This research aims to develop an ontology related to the domain of Balinese folklore. Balinese folklore is an important part of Bali's cultural heritage and has moral values, as well as being an inspiration in art and performance. Ontology is a method to organize and categorize information in a structured way, and has been widely applied in various fields. However, research on the ontology of Balinese folklore is still limited. This research will propose and develop a comprehensive and structured ontology model for Balinese folklore. The steps to be taken include analysis of relevant ontologies, development of an ontology schema, organization and classification of information, and testing and validation of the ontology model built. The method used in this research is methodology, which includes the stages of specification, knowledge acquisition, conceptualization, integration, evaluation, and documentation. The result of this research is a structured Balinese folklore ontology that has been evaluated using SPARQL queries. This ontology can be used as a source of information and reference in learning and utilizing Balinese folklore.